Piloting the Impact of Three Interventions on Guaiac Faecal Occult Blood Test Uptake within the NHS Bowel Cancer Screening Programme. (7th October 2015) - White, Becky; Power, Emily; Ciurej, Monika; Lo, Siu Hing; Nash, Katherine; Ormiston-Smith, Nick
Abstract : This study evaluated the impact of three interventions on uptake of the guaiac faecal occult blood test (gFOBT) in Greater London. The interventions were designed to improve awareness and understanding of the NHS Bowel Cancer Screening Programme (BCSP) and assist stool sampling. Logistic regression analysis of BCSP London data (N = 205, 541 invitees aged 60–74) compared uptake at 12 weeks between intervention groups and a control group, sent kits as usual between January-April 2013 and January-April 2014. An endorsement flyer, included with gFOBT kits, had no impact on uptake (P = 0.68 ). In 60–69-year-olds, there was a small but significant increase in modelled uptake amongst invitees sent both the flyer and a kit enhancement pack compared with controls (45.1% versus 43.4%, O R = 1.07, P = 0.047 ). In North East London, the flyer together with outdoor advertising was associated with a small but significant increase (45.6% versus 43.4%, O R = 1.09, P = 0.027 ). The largest increases were seen when all three interventions (flyer, pack, and advertising) were combined (49.5% versus 43.4%, O R = 1.28, P < 0.001 ). The increased uptake in the intervention groups was largest in "first-timers" and smaller amongst previous nonresponders and previously screened invitees.